2018
DOI: 10.1093/ecco-jcc/jjy144
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dimorphism in the Response to Broad-spectrum Antibiotics During T Cell-mediated Colitis

Abstract: While preliminary, our results suggest a differential response to both inflammation and Abx between male and female mice, The findings may be relevant to current practice and as the basis for further studies on the differential gender effects during long term antibiotic exposure in IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 65 publications
2
12
0
Order By: Relevance
“…Supplemented water was provided ad libitum and checked daily. Previously, we have described a sexual dimorphism in response to this antibiotic treatment [ 24 ]. Therefore, for this study, we chose only female mice to avoid confounding by sex.…”
Section: Methodsmentioning
confidence: 99%
“…Supplemented water was provided ad libitum and checked daily. Previously, we have described a sexual dimorphism in response to this antibiotic treatment [ 24 ]. Therefore, for this study, we chose only female mice to avoid confounding by sex.…”
Section: Methodsmentioning
confidence: 99%
“…In the acute DSS mouse colitis model, metronidazole treatment could prevent colonic in ammation, but has no therapeutic effect on established colitis [37]. Metronidazole in combination with cipro oxacin treatment resulted in expansion of Enterococcaceae and Lactobacillaceae in mice [33]. In our study, we found Enterobacteriaceae was also abundant after metronidazole treatment, and a bacterial strain E. ludwigii was identi ed to promote immune tolerance through increasing CD103 + DCs' ability to drive Treg differentiation independent of other intestinal ora.…”
Section: Discussionmentioning
confidence: 63%
“…Metronidazole, as a nitroimidazole preventing nucleic acid synthesis, limits anaerobic bacteria, protozoans and microaerophiles [33]. Metronidazole is medicative in active Crohn's colitis patients and preventive of post operative recurrence of CD in combination with other antibiotics, but has less bene t for ulcerative colitis [34].…”
Section: Discussionmentioning
confidence: 99%
“…Although GMB diversity in the mouse is relatively closer to that of man [ 68 , 69 ] we accepted both mouse and rat studies. We also accepted studies using any combinations of male or female animals, sexual dimorphism notwithstanding [ 44 , 53 , 70 ]. We did not consider metabolome data derived from matrices other than serum, given that changes across these compartments (eg, urine, feces) often correlate poorly [ 44 , 45 , 71 ].…”
Section: Discussionmentioning
confidence: 99%